2010
DOI: 10.1016/j.jhazmat.2009.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on influence of smoke venting velocity and vent height on mechanical smoke exhaust efficiency

Abstract: Abstract:A set of burning experiments were conducted to investigate the influence of smoke vent height and exhausting velocity on mechanical smoke exhausting efficiency.Results have shown that the smoke exhausting process becomes more efficient due to the increased smoke vent height and the decreased exhausting velocity, which eliminate the plug-holing issue with fewer disturbances on the smoke layer interface.For each certain exhausting velocity, there is a critical value of distance between the vent and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 9 publications
0
31
0
2
Order By: Relevance
“…Vauquelin et al [22] also noticed the plug-holing in some of the transverse smoke exhausting experiments in a small scale tunnel with less net height and concluded that in the cases with plug-holing, the smoke exhausting efficiency had strongly decreased. Ji et al [23] experimentally studied the influence of smoke vent height and exhausting velocity on mechanical smoke exhausting efficiency, and concluded that in the tests without plug-holing, the fresh air entrained due to smoke exhausting is up to 30% of the mechanical exhausting rate, and in order to achieve an excellent smoke exhausting, the amount of fresh air entrained due to smoke exhausting should be considered and reduced to minimum. However, in these former studies, delicate quantitative analyses on plug-holing induced by vertical shaft have rarely been addressed.…”
Section: Plug-holingmentioning
confidence: 99%
See 1 more Smart Citation
“…Vauquelin et al [22] also noticed the plug-holing in some of the transverse smoke exhausting experiments in a small scale tunnel with less net height and concluded that in the cases with plug-holing, the smoke exhausting efficiency had strongly decreased. Ji et al [23] experimentally studied the influence of smoke vent height and exhausting velocity on mechanical smoke exhausting efficiency, and concluded that in the tests without plug-holing, the fresh air entrained due to smoke exhausting is up to 30% of the mechanical exhausting rate, and in order to achieve an excellent smoke exhausting, the amount of fresh air entrained due to smoke exhausting should be considered and reduced to minimum. However, in these former studies, delicate quantitative analyses on plug-holing induced by vertical shaft have rarely been addressed.…”
Section: Plug-holingmentioning
confidence: 99%
“…However, if the shaft is so high that stack effect is strong enough to cause the occurrence of plug-holing, the lower fresh air will be directly exhausted and then the vertical shaft exhausts a mixture of smoky gases and clean air. Ji et al [23] experimentally studied the influence of smoke vent height and exhausting velocity on mechanical smoke exhausting efficiency, and concluded that once plug-holing occurs (with large exhausting velocity) due to the large amount of fresh air exhausted into the duct, less than half of the exhausting rate was smoke in the worst case. In addition, when plug-holing occurs, the disturbance on smoke-air interface enhances significantly (see Fig.…”
Section: Boundary Layer Separationmentioning
confidence: 99%
“…High-temperature smoke generated by tunnel fire hazard destroys the tunnel structure and its toxic components threaten personnel security greatly (Jie et al 2010). Related researches reported that 85% casualties in tunnel fire hazard are caused by high-temperature toxic smoke.…”
Section: .Introductionmentioning
confidence: 99%
“…Meanwhile, a research on the smoke exhaust systems for the smoke emission in the event of a fire in the building has been underway. In particular, an impact of the exhaust speed and the height of exhaust opening in a mechanical smoke exhaust system on the smoke exhaust performance has been investigated [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%